Implications Of Victim Precipitation On Imposing Criminal Sanctions For Perpetrator (Study In The City Of Purwokerto) - Hendriana, Rani; Retnaningrum, Dwi Hapsari; Puspita Sari, Dessi Perdani Yuris; Nuryanti, Imas Puji (Jurnal Dinamika Hukum, 2020)
The study of victim precipitation in Purwokerto is still lacking. Consequently, it is nearly impossible to get clear correlation between victim precipitation and the imposition of criminal senctions for perpetrators. The problems studied in this research are the implications of victim precipitation towards the imposition of criminal penalties for the perpetrators and factors that tend to impede the repercussions. This research used a qualitative research method, with juridical approach related to the imposition of a sentence for the perpetrator that is in the form of criminal punishment, which is lighter than prosecutor’s demand. However, not all judment of the judge include the victim precipitation aspect explicitly in considering the imposition of criminal sanctions. The legal substance aspect is the intervening factor, which is the specific minimum criminal threat that can override victim precipitation. Other contributing factors are the legal structure and the legal culture of the community.Keywords: perpetrators, implications, criminal sanctions, victim precipitation